Contemporary Management of Pulmonary Arteriovenous Malformations - Rauh, Nicholas; Gurley, John; Saha, Sibu (International Journal of Angiology, 2017)
Pulmonary arteriovenous malformations (PAVMs) are atypical vascular structures involving a direct connection between the pulmonary arterial and venous circulations. While PAVMs are a relatively uncommon disorder, unmanaged cases are at risk for the development of serious complications including embolization and infection. Since their first description in 1897, PAVMs have been identified and treated in a variety of ways. Advancements in diagnostic methods and operative techniques have allowed for more effective treatment of the disease. Most recently, the use of vascular plug transcatheter embolization has been described as an effective therapeutic procedure in the management of PAVMs. In this report, we present our experience with nine cases of PAVMs treated at the University of Kentucky, including special consideration of an exemplary case that illustrates the typical course of treatment for the disease.
Keywords: pulmonary arteriovenous malformations; transcatheter embolization therapy; vascular plug embolization; coil embolization; chest CT; pulmonary angiography; hereditary hemorrhagic telangiectasia